Fronto-insula network activity explains emotional dysfunctions in juvenile myoclonic epilepsy: Combined evidence from pupillometry and fMRI. (April 2015) - Paulus, Frieder Michel; Krach, Sören; Blanke, Marius; Roth, Christine; Belke, Marcus; Sommer, Jens; Müller-Pinzler, Laura; Menzler, Katja; Jansen, Andreas; Rosenow, Felix; Bremmer, Frank; Einhäuser, Wolfgang; et al.
Abstract: Emotional instability, difficulties in social adjustment, and disinhibited behavior are the most common symptoms of the psychiatric comorbidities in juvenile myoclonic epilepsy (JME). This psychopathology has been associated with dysfunctions of mesial-frontal brain circuits. The present work is a first direct test of this link and adapted a paradigm for probing frontal circuits during empathy for pain. Neural and psychophysiological parameters of pain empathy were assessed by combining functional magnetic resonance imaging (fMRI) with simultaneous pupillometry in 15 JME patients and 15 matched healthy controls. In JME patients, we observed reduced neural activation of the anterior cingulate cortex (ACC), the anterior insula (AI), and the ventrolateral prefrontal cortex (VLPFC). This modulation was paralleled by reduced pupil dilation during empathy for pain in patients. At the same time, pupil dilation was positively related to neural activity of the ACC, AI, and VLPFC. In JME patients, the ACC additionally showed reduced functional connectivity with the primary and secondary somatosensory cortex, areas fundamentally implicated in processing the somatic cause of another's pain. Our results provide first evidence that alterations of mesial-frontal circuits directly affect psychosocial functioning in JME patients and draw a link of pupil dynamics with brain activity during emotional processing. The findings of reduced pain empathy related activation of the ACC and AI and aberrant functional integration of the ACC with somatosensory cortex areas provide further evidence for this network's role in social behavior and helps explaining the JME psychopathology and patients' difficulties in social adjustment.